Measurement of the electric energy storage capacity in solar thermoelectric generators’ energy harvesting modules - Pedro C Dias; Flávio JO Morais; Luis FC Duarte; Maria Bernadete M França; Anderson W Spengler; Andreu Cabot (International Journal of Distributed Sensor Networks)
Reducing energy consumption is mandatory in self-powered sensor nodes of wireless sensor networks that obtain all their energy from the environment. In this direction, one first step to optimize the network is to accurately measure the total energy harvested, which will determine the power available for sensor consumption. We present here a technique based on an embedded circuit with an ultra-low-power microcontroller to accurately measure the efficiency of flat-panel solar thermoelectric generators operating with environmental temperature gradients. Experimental tests showed that when a voltage of 180 mV (best case in an environmental flat-panel solar thermoelectric generators) is applied to the input of the DC–DC converter, the proposed technique eliminates a measurement error of 33% when compared with the conventional single supercapacitor strategy.